2015
DOI: 10.1002/adma.201500141
|View full text |Cite
|
Sign up to set email alerts
|

High‐Order Non‐Linear Optical Effects in Organic Luminogens with Aggregation‐Induced Emission

Abstract: 2,3-bis(4-(phenyl(4-(1,2,2-triphenylvinyl)phenyl)amino)phenyl)fumaronitrile (TTF) shows unique aggregation-induced emission (AIE) characteristics. Under the excitation of a 1560 nm femtosecond laser, simultaneous three-photon-excited luminescence (3PL) and third-harmonic-generation signals can be observed from its nanoaggregate and the solid state. TTF is further encapsulated with DSPE-mPEG (a type of amphiphilic polymer) to form AIE-active nanoparticles. 3PL brain imaging of mice is achieved based on the nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 30 publications
(26 reference statements)
1
78
0
Order By: Relevance
“…The values of δ and Φδ are much higher than the widely used commercial dyes, such as Evans Blue and other nanoparticles in the literatures. 26,28,38,[45][46][47] These results indicate that PIPBT-TPE dots and PITBT-TPE dots are promising luminescent reagents for TPA imaging.…”
Section: Resultsmentioning
confidence: 78%
“…The values of δ and Φδ are much higher than the widely used commercial dyes, such as Evans Blue and other nanoparticles in the literatures. 26,28,38,[45][46][47] These results indicate that PIPBT-TPE dots and PITBT-TPE dots are promising luminescent reagents for TPA imaging.…”
Section: Resultsmentioning
confidence: 78%
“…55 A series of non-linear optical characterization experiments were performed to see if the TPE-TETRAD NPs possess similar characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…7E. 55 We propose that THG photons are directly generated under femtosecond excitation and may be reabsorbed by the TPE-TETRAD molecules in NPs to produce fluorescence in a process known as THG-induced fluorescence. This may be a more efficient pathway to achieve 3PL signals, since direct 3PL is a fifth-order non-linear optical process, while 3PL induced by one-photon excitation of THG is a linear absorption based on a third-order NLO process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to great potential in two‐photon fluorescence bioimaging of TPETPAFN dots, Qian et al further found that these dots possess excellent three‐photon and even four‐photon absorption and fluorescence properties, owing to the extend π‐conjugation and electron‐donor and acceptor interaction in TPETPAFN molecule . The three‐photon fluorescence as well as third harmonic generation (THG) of TPETPAFN are enhanced as the aggregates form, under fs laser excitation at 1560 nm.…”
Section: Optical Property and Application Of Fluorescent Organic Dotsmentioning
confidence: 99%